Microwave irradiation is a suitable method for caulerpin extraction from the green algae Caulerpa racemosa (Chlorophyta, Caulerpaceae). Issue 8 (18th April 2022) - Cantarino, Sarah J.; Coutinho, Ricardo; Soares, Angélica R.; Duarte, Heitor M.; Martinez, Sabrina T.
Abstract: Caulerpin is a bisindolic alkaloid that has been obtained from many species of the genus Caulerpa . The main objective of this paper is to evaluate four extraction methods of caulerpin in the C. racemosa: maceration (DMA), Soxhlet extraction (SOX), ultrasound-assisted extraction (UAE) and microwave-assisted extraction (MAE). The methods were compared through caulerpin content quantified by Ultraviolet-visible (UV-vis) spectrophotometry. The highest extract yield was obtained by SOX but the highest contain of caulerpin was presented in the MAE extract. The caulerpin content was significant different within the extacts by MAE and UAE, it yielded by MAE more than three times as much as UAE. The most efficient caulerpin extraction method had the parameters solvent, temperature and time optimised. Thus, the best conditions were achieved with MAE in ethanol during 7 min at 90 °C. Therefore, this work suggests an improved routine analysis of caulerpin by the green chemistry concept. Graphical Abstract: